ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS DI TINJAU DARI GAYA KOGNITIF SISWA SMP PADA MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBASIS ETNOMATEMATIKA - Rizka Alfami Majidi; Yanti Mulyanti; Aritsya Iswatama (CV. ADIBA AISHA AMIRA, 2025)
This study aims to determine the ability of mathematical creative thinking in terms of the cognitive style of junior high school students in the ethnomathematics-based project based learning model. The type of research used is qualitative research with test and interview instruments. The population used as a sample in this study is all students of class VII of SMP Negeri 5 Geger Bitung, Sukabumi Regency. The data analysis used is data reduction, data presentation, and drawing conclusions. Based on the data analysis, it was obtained that: Subjects with high mathematical abilities on average carry out creative thinking processes to be able to understand problems, practice concepts, solve problems, and connect one problem to another, in the reasoning process to be able to analyze assumptions, plan processes, solve problems, and draw conclusions. Furthermore, subjects with moderate mathematical abilities can only carry out creative thinking processes to understand problems and solve problems. These subjects can also only carry out the reasoning process to reach assumptions and do not determine generalizations correctly. Finally, for students who have low mathematical abilities, on average, their creative thinking ability only reaches as far as understanding the problem and cannot practice the concept, and students in reasoning only reach as far as determining initial guesses and they find it difficult to convey the results of their answers during interviews.